Analisis Penguatan Kompetensi Komunikasi Bhabinkamtibmas dalam Mendukung Keamanan dan Ketertiban Masyarakat - Achmad Zuhri; Maya Sandra Rosita Dewi; Rahmah Attaymini (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2026)
Bhabinkamtibmas holds a strategic role in maintaining public security and social order at the village level. However, the effectiveness of this role is closely related to the officers’ communicative capacity in delivering messages, building trust, and responding to community dynamics. This community service article aims to analyze the implementation of effective communication training as an effort to strengthen the capacity of Bhabinkamtibmas in Kecamatan Klaten Utara, Kabupaten Klaten. The activity employed a descriptive qualitative design through Focus Group Discussion (FGD), observation, documentation, and interactive training sessions involving 25 Bhabinkamtibmas personnel from two police sectors. The program focused on public speaking, self-development, self-acceptance, and strategies for effective public communication. The findings indicate that the training improved participants’ understanding of persuasive and humanistic communication, strengthened their confidence in interacting with the public, and expanded their practical strategies for addressing communication barriers in the field, especially public distrust and weak message reception. The activity also demonstrates that strengthening communicative competence is an important element in supporting Bhabinkamtibmas’ public service role and in fostering more adaptive approaches to maintaining community security and order.